Disaster Management in Indonesia: A Lesson from the 2010 Eruption of Mount Merapi - Iqbal, Muhammad (Unisia, 2021)
One of the most significant eruptions of Merapi that occurred was the eruption of Merapi in October November 2010 (Pallister, et al. 2013). At that time, the impact of the eruption of Merapi was tremendous. The flow of hot clouds swept the area on the slopes of Merapi. The cleaning of the hot clouds also caused casualties, either death or injury. The eruption of Merapi in 2010, which is indicated as a 100-year eruption period, caused extensive and massive damage and loss of community livelihood assets. Damage and loss assessment is divided into 5 (five) sectors: settlement, infrastructure, social, economy and cross-sector. This research is a qualitative descriptive study. this study uses information on websites, in newspapers, and government reports. These data are used to support the statements given by the interviewees. All documents processed through the NVivo application. The finding of this article is Local governments are considered slow in responding and distributing information. Apart from that, the problem of limited resources has resulted in the obstruction of resource mobilization. Budget constraints, disruption of regional government functions, and the insufficient number of government human resources have resulted in slow mobilization. However, the local government succeeded in optimizing NGO’s / NPO’s and also volunteers in emergency response efforts. Finally, the government’s slow performance was covered by NPO’s/NGO’s and volunteers. NPOs/NGOs and volunteers have a very significant role in the emergency response to the eruption of Mount Merapi.